2015
DOI: 10.1111/febs.13612
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical modeling of hematopoietic stem cell transplantation – advantages and limitations

Abstract: Hematopoietic stem cell transplantation, which was first successfully performed in the 1950s, remains a critical therapeutic modality for treatment of a diverse array of diseases, including a multitude of hematological malignancies, autoimmune disorders, amyloidosis and inherited genetic hematological disorders. Although great advances have been made in understanding and application of this therapy, significant complications still exist, warranting further investigation. Of critical importance, graft‐versus‐ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 57 publications
(55 reference statements)
0
29
0
1
Order By: Relevance
“…Additionally, several studies demonstrated, the regenerative function of these cells in damaged tissues (Narazaki & Cristante 2011, Ryu et al 2012, Bittencourt et al 2016, Stolfi et al 2016.…”
Section: Topic Of General Interestmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, several studies demonstrated, the regenerative function of these cells in damaged tissues (Narazaki & Cristante 2011, Ryu et al 2012, Bittencourt et al 2016, Stolfi et al 2016.…”
Section: Topic Of General Interestmentioning
confidence: 99%
“…(Friedenstein et al 1974, Tharasanit et al 2011, Rici et al 2012, Kim et al 2013, Hu et al 2014 postnatal life, is the most studied, having two lines of stem cells: hematopoietic stem cells (HSC) and mesenchymal stem cells (MSC) (Bittencourt et al 2006, BydlowskI et al 2009, Narazaki & Cristante 2011 (Fig.1 and 2). Furthermore, BMSC is the main source of stem cells, because of its easy isolation, and more than one to six millions of mesenchymal or/and hematopoietic stem cell can be isolated, cultured and applied without problem from one isolation (Oliveira et al 2010, Ryu et al 2012, Bittencourt et al 2016, Stolfi et al 2016.…”
Section: Topic Of General Interestmentioning
confidence: 99%
See 3 more Smart Citations